2016
DOI: 10.1515/johr-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plant Growth Promoting Bacteria on Transplants Growth and Lettuce Yield in Organic Production

Abstract: Application of beneficial bacterial strain B125 (Enterobacter sp.) and strain PZ9 (Bacillus sp.) in lettuce transplants production significantly enhanced seed germination and plant biomass. The best effect was obtained when the mixture of B125 and PZ9 was used. Combined application of these bacteria significantly increased transplants biomass, which was about 45% higher than that in the control. However, after planting these transplants in organic field, generally, there were no differences in yield and nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
6
1
Order By: Relevance
“…In the control treatment, the highest vitamin C content was measured in autumn (short day). Similar results, where the highest vitamin C content in lettuce head was obtained in the control treatment, were significantly different from the treatment with bacterial strains (Szczech et al, 2016). This result is in contradiction with the results of Fu et al (2017), which imply that vitamin C content is increased with a high light intensity.…”
Section: Resultscontrasting
confidence: 78%
See 3 more Smart Citations
“…In the control treatment, the highest vitamin C content was measured in autumn (short day). Similar results, where the highest vitamin C content in lettuce head was obtained in the control treatment, were significantly different from the treatment with bacterial strains (Szczech et al, 2016). This result is in contradiction with the results of Fu et al (2017), which imply that vitamin C content is increased with a high light intensity.…”
Section: Resultscontrasting
confidence: 78%
“…The application of two Trichoderma harzianum strains (T969 and T447) showed a higher concentration of phosphorus (P) and potassium (K + ) in the shoots and roots of tomato seedlings (Azarmi et al, 2011). A synergistic effect of two bacterial strains stimulated nitrogen uptake by plants treated with microbiological fertilisers as transplants (Szczech et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This intensive system of lettuce production has a high demand for nutrients in the form of fertilizers and agrochemicals to avoid pests and diseases in both crop stages [ 22 ]. It has been reported that lettuce crops show a favorable response after inoculation with a single or a mixture of PGPB of different genera such as Azospirillum , Azotobacter , Pseudomonas , Rhizobium and Bacillus , among others [ 18 , 23 , 24 , 25 , 26 , 27 ], even in combination with fungi [ 28 ]. Such treatments led to larger plants with more biomass, but other aspects also were affected, such as the germination rate.…”
Section: Introductionmentioning
confidence: 99%